An experience of radiofrequency ablation in the treatment of renal cell carcinoma - P. V. Glybochko; Yu. G. Alyaev; S. A. Kondrashin; N. I. Sorokin; E. V. Shpot’; G. A. Martirosyan (Сеченовский вестник, 2014)
Radiofrequency ablation is a minimally invasive treatment for local destruction, widely used in the combined treatment of kidney cancer. Application of radiofrequency ablation allowed to expand the indications for more radical treatment of kidney tumors in patients who may not perform traditional nephrectomy or partial nephrectomy due to extremely burdened somatic status. Efficacy and safety of RFA greatly increased when it is combined with presuperselective occlusion of blood vessels that feed the tumor. We have experience in the use of superselective embolization in combination with RFA when a kidney tumor is in two patients. In both observations obtained good results of combined treatment. In some patients, this combination (CCE + RFA) may be an alternative to open surgery, thus expanding the range of modern minimally invasive treatments for kidney tumors.